Copyright and Digitization and Preservation of State Government Documents: A Detailed Analysis - Currier, Brett D.; Gilliland, Anne; Hansen, David R. (Journal of Copyright in Education & Librarianship, 2016)
This paper builds off "Copyright and the Digitization of State Government Documents: A Preliminary Analysis" presented at IPres 2015. In this paper, we present a more detailed analysis and a practical framework for local archivists and librarians to use in assessing copyright status, the application of fair use, and use of other copyright limitations to different types of government documents.